Direct gem-difluoromethylenation of sp3-hybridized carbon center through copper-mediated radical/radical cross-coupling for the construction of a CH2–CF2 linkage. Issue 87 (27th August 2015) - Jiang, Haizhen; Xu, Minjun; Lu, Wenjun; Tian, Wenfeng; Wan, Wen; Chen, Yunrong; Deng, Hongmei; Wu, Shaoxiong; Hao, Jian
Abstract : An efficient gem -difluoromethylenation of benzyl bromides through copper-mediated direct radical/radical C–C cross-coupling has been developed for the construction of CH2 –CF2 linkage. Abstract : Efficient direct gem -difluoromethylenation of an sp 3 -hybridized carbon center in benzyl bromides using benzo-1, 3-azolic (oxa-, thia- or aza-) difluoromethyl bromides for construction of a CH2 –CF2 linkage has been developed through radical/radical C–C cross-coupling via two separate single electron transfer processes (SET) under the promotion of different copper sources.